Investigation of thin sheet formability (copper) during laser shock forming - Nurul Farhana Abdul Rahman. (2012)
Laser shock forming (LSF) is a sheet metal forming process which includes high-pressure, high strain rate and non-contact loading. A new forming process, Flexible Die Laser Shock Forming (FDLSF), without dies is developed. This new forming method uses laser-induced shock pressure to shape a sheet metal without complex or intricate forming equipments. However, formability of metal foils during the developed process is not yet investigated.